Optimal reinsurance: A risk sharing approach - Alejandro Balbas; Beatriz Balbas; Raquel Balbas (Risks, 2013)
This paper proposes risk sharing strategies, which allow insurers to cooperate and diversify non-systemic risk. We deal with both deviation measures and coherent risk measures and provide general mathematical methods applying to optimize them all. Numerical examples are given in order to illustrate how efficiently the non-systemic risk can be diversified and how effective the presented mathematical tools may be. It is also illustrated how the existence of huge disasters may lead to wrong solutions of our optimal risk sharing problem, in the sense that the involved risk measure could ignore the existence of a non-null probability of 'global ruin' after the design of the optimal risk sharing strategy. To overcome this caveat, one can use more conservative risk measures. The stability in the large of the optimal sharing plan guarantees that 'the global ruin caveat' may be also addressed and solved with the presented methods.
Keywords: 330; optimal reinsurance; general risk measure; risk sharing; systemic risk